Study Study The Effect of Lambing Type and Ewes Age in Percentage of Total Solid and Total Milk Yield For Arrabi Sheep Milk: Study The Effect of Lambing Type and Ewes Age in Percentage of Total Solid and Total Milk Yield For Arrabi Sheep Milk - AL-yasery, Ahmed J.; Albrkat, Hadi Awad; AL-Saadon, Ali Abdullah; Shaker, Basim F. (Journal of Kerbala for Agricultural Sciences, 2018)
Abstract: This study was carried out in animal filed in agricultural experiments and research station in Agriculture college / Al-Muthanna University from 10/11/2016 to 10/2/2017 to investigate the effect of lambing type (single and twins birth) and ewes mothers age in percentage of total solid (fatty and non-fatty) and total milk yield of Arrabi sheep milk , in study used 30 Arrabi gimmers newly lambed with its single and twins lambs at ages 1.5 , 2 and 3 years placed in typical yards in hygienic conditions and submitted to supportive vaccination and therapeutic program to ensure the safety and not presence any diseases , the milk samples were taken since the first week after lambing until 10 weeks and recorded the total milk yield and composition weekly during experiment period . the results showed presence the significantly difference at (P≤ 0.05) between the studied values and the ratio of fat in milk which 8.89 at first week to 6.17at tenth week in single , while these values was 8.14at first week to 6.04at tenth week to twins , then ratio of milk fat elevated in single compare with twins , then the ratio of solid materials in milk was 13,90 to 14,87 in single and 30,13 to 16 in twins and also in total yields of milk each week from the first to tenth weeks . the result showed presence of significant correlation between animals , in conclusion , the lambing type and the ewes age that effected on the percentage of fat , non-fatty solid materials ratio and total yield of milk each week in the studied animals (Arrabi sheep) .